Selectfluor™-Catalyzed Synthesis of N-Sulphonyl Imines - Wu, Liqiang; Cui, Taizhen; Ma, Weiwei; Yan, Fulin (Asian Journal of Chemistry, 2010)
A new and simple synthesis of N-sulphonyl imines has been accomplished by reaction of sulphonamides with aryl aldehydes in the presence of Selectfluor™ under solvent-free conditions.